Repurposing hyperpolarization‐activated cyclic nucleotide‐gated channels as a novel therapy for breast cancer - Mok, Ka‐Chun; Tsoi, Ho; Man, Ellen PS; Leung, Man‐Hong; Chau, Ka Man; Wong, Lai‐San; Chan, Wing‐Lok; Chan, Sum‐Yin; Luk, Mai‐Yee; Chan, Jessie Y.W.; Leung, Jackie K.M.; Chan, Yolanda H.Y.; et al. (Clinical and translational medicine, 2021)
Hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels are members of the voltage‐gated cation channel family known to be expressed in the heart and central nervous system. Ivabradine, a small molecule HCN channel‐blocker, is FDA‐approved for clinical use as a heart rate‐reducing agent. We found that HCN2 and HCN3 are overexpressed in breast cancer cells compared with normal breast epithelia, and the high expression of HCN2 and HCN3 is associated with poorer survival in breast cancer patients. Inhibition of HCN by Ivabradine or by RNAi, aborted breast cancer cell proliferation in vitro and suppressed tumour growth in patient‐derived tumour xenograft models established from triple‐negative breast cancer (TNBC) tissues, with no evident side‐effects on the mice. Transcriptome‐wide analysis showed enrichment for cholesterol metabolism and biosynthesis as well as lipid metabolism pathways associated with ER‐stress following Ivabradine treatment. Mechanistic studies confirmed that HCN inhibition leads to ER‐stress, in part due to disturbed Ca2+ homeostasis, which subsequently triggered the apoptosis cascade. More importantly, we investigated the synergistic effect of Ivabradine and paclitaxel on TNBC and confirmed that both drugs acted synergistically in vitro through ER‐stress to amplify signals for caspase activation. Combination therapy could suppress tumour growth of xenografts at much lower doses for both drugs. In summary, our study identified a new molecular target with potential for being developed into targeted therapy, providing scientific grounds for initiating clinical trials for a new treatment regimen of combining HCN inhibition with chemotherapy. Overexpression of HCN provides advantages for the survival and proliferation of cancer cells. The addition of Ivabradine blocks HCN channels and affects intracellular homeostasis of Ca2+. Subsequently, this induces ER‐stress and triggers apoptosis. Also, it makes the cancer cells become more sensitive to other chemotherapeutic agents.